Halide perovskite-based indoor photovoltaics: recent development and challenges - Bening Tirta Muhammad (2022)
Metal halide perovskite solar cell (PSC) technology is yet to make its way to enter the outdoor solar energy harvesting market as a single junction or a tandem cell; recent studies have already sparked huge interest in PSC for indoor photovoltaic (iPV) applications. The spark is further amplified by the vision of extensive use of low power Internet of Things (IoT) sensors in smart and sustainable buildings. To date, halide perovskite-based solar cells have exceeded 40% efficiency in indoor lighting, which is way above other emerging PV cells such as organic photovoltaic cells and dye-sensitized solar cells. Thanks to tremendous efforts on defect reduction and interfacial engineering in the field of PSCs, the strategies can be directly applied to low light intensity indoor settings where defect and trap states are very detrimental to device performance. Here, we summarize the recent developments of PSCs for iPV applications with emphasis on device engineering approaches and feasibility of PSCs to power smart sensors in indoor setting. We also provide a technical explanation for indoor light profile and respective iPV cell efficiency measurement. Last, we discuss existing challenges in halide perovskite-based iPV cells and an outlook to pave the way for PSC to enter the trillion dollar-sized IoT market by 2025.